Purification of DNA for bacterial productivity estimates. - Burnison, B K (1990)
[methyl-3H]thymidine-labeled DNA from natural populations of aquatic bacteria was completely separated from RNA and protein by hydroxylapatite chromatography. The procedure was validated by monitoring increases in Escherichia coli cell count, A550, DNA concentration, and thymidine incorporation into DNA isolated by the proposed technique. The procedure can be used in the field and does not rely on the use of acid-base hydrolysis or volatile organic solvents.